2014
DOI: 10.1016/j.actpsy.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and unique representations of two-digit decimals

Abstract: We examined the representation of two-digit decimals through studying distance and compatibility effects in magnitude comparison tasks in four experiments. Using number pairs with different leftmost digits, we found both the second digit distance effect and compatibility effect with two-digit integers but only the second digit distance effect with two-digit pure decimals. This suggests that both integers and pure decimals are processed in a compositional manner. In contrast, neither the second digit distance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In contrast, decimal comparison is much less studied and while some studies have examined magnitude based processing (Kallai & Tzelgov, 2014;Zhang, Chen, Lin, & Szucs, 2014), to my knowledge, none have explicitly contrasted whole vs. rational distance effects in this notation. Decimals are a ripe area for future research as the stimuli space affords greater opportunities for orthogonalizing distance dimensions.…”
Section: Magnitude Representations Of Symbolic Rational Number Quantitiesmentioning
confidence: 99%
“…In contrast, decimal comparison is much less studied and while some studies have examined magnitude based processing (Kallai & Tzelgov, 2014;Zhang, Chen, Lin, & Szucs, 2014), to my knowledge, none have explicitly contrasted whole vs. rational distance effects in this notation. Decimals are a ripe area for future research as the stimuli space affords greater opportunities for orthogonalizing distance dimensions.…”
Section: Magnitude Representations Of Symbolic Rational Number Quantitiesmentioning
confidence: 99%
“…Only recently, research in numerical cognition investigated the processing of decimal numbers in adults (Cohen, 2010; DeWolf, Grounds, Bassok, & Holyoak, 2014; Ganor-Stern, 2013; Huber, Klein, Willmes, Nuerk, & Moeller, 2014a; Iuculano & Butterworth, 2011; Kallai & Tzelgov, 2014; Varma & Karl, 2013; Zhang, Chen, Lin, & Szűcs, 2014). Findings are inconsistent so far, indicating that decimal numbers and natural numbers either share or differ in processing characteristics.…”
Section: Decimal Numbersmentioning
confidence: 99%
“…Using the automatic processing paradigm where the numerical magnitude of decimals is task irrelevant, Kallai and Tzelgov (2014) showed that decimals are not represented well enough to be automatically activated as integers. In addition, three studies observed a smaller compatibility effect for decimals than for integers (Huber, Klein et al, 2014;Varma & Karl, 2013;Zhang et al, 2014).…”
mentioning
confidence: 99%
“…In contrast to abundant studies of fractions, only a few studies have investigated the mental representation of decimals (Cohen, 2010;Huber, Klein, Willmes, Nuerk, & Moeller, 2014;Kallai & Tzelgov, 2014;Varma & Karl, 2013;Zhang, Chen, Lin, & Szűcs, 2014). These studies have addressed whether the representation of decimals is similar to that of multidigit integers by examining the distance effect and/or the compatibility effect.…”
mentioning
confidence: 99%